Observations on Uncertainty. (March 2017) - Bloom, Nicholas
Abstract: I discuss three phenomena which appear important for modelling the impact of uncertainty on growth. The first is international spillovers in uncertainty, which arise even in large countries like the United States and particularly in smaller countries like Australia. Second, that the main channel for uncertainty to impact gross domestic product growth is through investment, which responds much more strongly and rapidly than consumption expenditure. This is possibly because firms are more forward‐looking than consumers, so respond more strongly to changes in future expectations of business conditions. Third, I discuss how recently uncertainty has spiked in three waves: the great recession of 2008–2009, the fiscal crises in the United States and Europe from 2010 to 2012 and recently after the Brexit and Trump votes.